At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
Step-by-step explanation:
I assume that you mean y = x²/(x²+1), not y = x²/x²+1.
x²+1 = 0
x² = -1
x = ±√(-1) = ±i
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.